2022
DOI: 10.1017/aee.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

Water education and water culture in curricula for Primary, Middle and upper Secondary school levels

Abstract: With water shortage and increasing demand for water, education may have an important role in promoting the sustainable management of water resources. Educational curricula are the key resources used by teachers for studentsʼ teaching and training purposes. This study assessed water culture and water education-related criteria and standards in programmes and school curricula for Primary, Middle and upper Secondary school education in Morocco. It also investigated teachers for suggestions and views regarding met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The water cycle is supposed to be taught in Australian schools around Grade 7, embedded as it is in the science, humanities and social science (HASS), and geography National Curriculum, and in Grade 9 geography, although this might not be the case in all countries around the world; for example, it was not explicit in Moroccan curricula in 2023 [56]. Australian students are supposed to be introduced to the processes of the water cycle in the circulation of water through the Earth's atmosphere, its surface, and the sub-surfaces that tap into the vast ocean stores, the large bodies of ice and water basins deep within the ground.…”
Section: Water Literacy In the Context Of Climate Change Redefined Th...mentioning
confidence: 99%
“…The water cycle is supposed to be taught in Australian schools around Grade 7, embedded as it is in the science, humanities and social science (HASS), and geography National Curriculum, and in Grade 9 geography, although this might not be the case in all countries around the world; for example, it was not explicit in Moroccan curricula in 2023 [56]. Australian students are supposed to be introduced to the processes of the water cycle in the circulation of water through the Earth's atmosphere, its surface, and the sub-surfaces that tap into the vast ocean stores, the large bodies of ice and water basins deep within the ground.…”
Section: Water Literacy In the Context Of Climate Change Redefined Th...mentioning
confidence: 99%
“…Education plays an important role in disseminating this knowledge to society, especially the younger generation, so that they can respect, understand and follow sustainable practices in watershed management. Through education, we can create awareness of the importance of preserving river watersheds and develop innovative solutions that combine local wisdom and the latest science in sustainable management of river watersheds (Ahmed et al, 2020;Khiri et al, 2023).…”
Section: Contributions and Recommendationsmentioning
confidence: 99%
“…In Malaysia, Kanniah et al (2001), carried out a study and concluded that the geotechnologies course with focus on Remote Sensing (RS), uses the "direct experience method", i.e., the graduate has a direct and associated learning of environmental problems of the place where they live, besides manipulating the GIS/SIG, but this depends on the educational process that each country adopts. In Morocco, Khiri et al (2022), reported that the problem is the curricular adaptation to the use of this type of tool, since the subject "environmental education", only contemplates other subjects such as "child at school" "child, environment, and nature" "agriculture and environmental protection".…”
Section: International Contextmentioning
confidence: 99%